Party images in Northern Ireland: evidence from a new dataset. Issue 1 (2nd January 2019) - Coakley, John; Garry, John; Matthews, Neil; O'Leary, Brendan
ABSTRACT: The literature on belief systems in mass publics shows that survey respondents typically have difficulty in describing their images of political parties; only about half offer a meaningful description of how they see individual parties. This paper investigates what people in Northern Ireland think that parties stand for in their home jurisdiction, in Great Britain and in the Republic of Ireland, using open-ended questions in a survey of 1, 008 Northern Ireland residents. Northern Ireland respondents resemble those elsewhere, in that only about half seem able to offer a politically meaningful description of what local parties stand for. Among the more politically sophisticated, the Northern Ireland parties are described in ethnonational terms, the British parties are placed in socio-economic (social class and left-right) categories, but few respondents know how to describe the parties in the Republic of Ireland. There is an intriguing asymmetry in the characterization of Northern Ireland's unionist and nationalist parties: the DUP emerges as only marginally more 'hard-line' than the UUP, whereas a great gulf exists between the SDLP and Sinn Féin, the former being perceived as much more moderate. Notwithstanding high levels of electoral stability in Northern Ireland, our findings show that party supporters vary greatly in their levels of political sophistication, perhaps allowing elites greater freedom of action than if all voters were highly politically informed.